SYSTEM DYNAMICS USE IN BLOGOSPHERE DEVELOPMENT SIMULATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Today the Latvian blogosphere is a community of almost 200 000 blogs. Blogs have become an important part of news agencies and web portals because they deliver information to the reader faster than traditional media. To forecast the computational resources and necessary funding for community development, it is necessary to design an evolutional model based on the data collected and give an insight into its evolution ways.